THE INFLUENCE OF SERVICE QUALITY ON CONSUMER SATISFACTION AT THE GANDA BAKERY IN PEMATANG SIANTAR - Dian Pertiwi; Mariyudi; Adnan; Heriyana (RADJA PUBLIKA, 2024)
This research aims to find out how service quality influences consumer satisfaction at the Ganda Bakery in Pematangsiantar. The consumer satisfaction indicators used consist of fulfilling consumer expectations, attitude or desire to use the product, recommending to other parties, service quality, loyalty, good reputation, location. then the indicators of reliability used consist of compliance with promises, responsibility, good impression, punctuality, appropriate information. The indicators of responsiveness used consist of fast service, helping consumers, responsive handling of responses. Indicators of assurance consist of communication, credibility, security, competence. Indicators of empathy consist of access, communication, ability to understand customers. Furthermore, indicators of physical evidence consist of the latest or newest equipment, attractive physical facilities, neat appearance and appropriate physical facilities. Where all these variables will be used using the Likert scale. The data used in this study is primary data obtained by distributing questionnaires to 130 consumers who buy at Ganda Bakery in Pematangsiantar. The data analysis technique used in this study is multiple linear regression analysis using the help of SPSS software version 25. The results showed that reliability, responsiveness, assurance, emphaty and physical evidence partially had a positive and significant effect on the consumer satisfaction at the Ganda Bakery in Pematangsiantar.